MARINE-LENHART SYNDROME WITH COEXISTING METASTATIC PAPILLARY THYROID CARCINOMA - Ahmadi, Affan; Kusumawati, Maya; Ritonga, Ervita; Soetedjo, Nanny NM; Permana, Hikmat (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE Graves’ disease with accompanying autonomously functioning thyroid nodules (AFTN) is known as MarineLenhart Syndrome (MLS). Malignant nodules can coexist with MLS. Papillary Thyroid Carcinoma (PTC) with distant metastases could cause serious complications. A 43-yearold Indonesian female developed hyperthyroidism due to the coexistence of Graves’ disease and AFTN (MLS) in the right lobe of the Thyroid gland. A suspicious malignant nodule was located on the other side of the thyroid, which was detected by thyroid scanning. A total thyroidectomy was performed and thyroid tissue was histologically diagnosed as papillary thyroid carcinoma. We report the presence of PTC with intrapulmonary metastases in MLS.